ADAT ISTIADAT PERNIKAHAN DESA KOTO JAYO KECAMATAN TANAH TUMBUH KABUPATEN BUNGO 1960 – 1980 - Erik Julianda, Ulul Azmi (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2018)
Abstract                    This study aims to find out the customs of marriage, Koto Jayo village, Tanah Tumbuh sub-district, Bungo district, 1960s-1980s. The research method used is the historical method, including the stages of heuristics, criticism, interpretation and histeriography. Sources of data obtained from books and archives related to traditions in the village of Koto Jayo, a growing land district in Bungo district, as well as interviews with traditional leaders, experts, and local residents. This research is a type or writing of history, which will discuss how the history of the village of Koto Jayo relates to the history of the customs of the local wedding.               The results showed that for the present condition of the Koto Jayo village tradition for some people began to abandon their old traditions this was due to the times and technological advances and the few people who preserve their culture and the entry of foreign culture into the traditions of Koto Jayo village such as Minang and Javanese culture so that cultural acculturation or cultural mixing with one another occurs. However, this does not eliminate the characteristics of the local culture and over time the tradition of the village of Koto Jayo becomes a modren.               In preserving the tradition of the village of Koto Jayo, it has not been optimally carried out by community leaders and the Bungo Regency Cultural Service. This is still a lot of young people today do not know their traditions and customs because the lack of public awareness to preserve ancestral culture. in preserving culture, especially in the village of Koto Jayo.Keywords: Customary History of Marriage, Koto Jayo Village Tanah Tumbuh Subdistrict, District Bungo. Abstrak            Penelitian ini bertujuan untuk mengetahui  adat istiadat pernikahan, desa Koto Jayo kecamatan Tanah Tumbuh kabupaten Bungo 1960an-1980an. Metode penelitian yang digunakan adalah metode sejarah, meliputi tahapan heuristik, kritik, interpretasi dan histeriografi. Sumber data yang didapat dari buku dan arsip yang berkaitan dengan tradisi di desa koto jayo kecamatan tanah tumbuh kabupaten bungo, serta wawancara dengan tokoh adat, para pakar, dan warga sekitar. Penelitian ini merupakan jenis atau penulisan sejarah, yang akan membahas bagaimana sejarah desa koto jayo yang berhubungan dengan sejarah adat istiadat pernikahan penduduk setempat.Hasil penelitian menunjukan bahwa untuk kondisi sekarang ini tradisi desa Koto Jayo bagi sebagian orang mulai meninggalkan tradisi lamanya hal ini di karenakan perkembangan zaman dan kemajuan teknologi dan sedikitnya orang yang melestarikan budaya mereka serta masuknya budaya luar ke dalam tradisi desa koto jayo seperti budaya minang dan jawa sehingga terjadi akulturasi budaya atau percampuran budaya satu dengan budaya lainnya. Meskipun begitu hal ini tidak menghilangkan ciri khas budaya setempat dan seiring berjalannya waktu tradisi desa koto jayo menjadi modren.Dalam melestarikan tradisi desa koto jayo belum optimal dilakukan oleh tokoh masyarakat dan dinas kebudayaan kabupaten bungo hal ini masih banyaknya anak muda zaman sekarang tidak tau tradisi serta adat istiadat mereka karena kurangnya kesadaran masyarakat untuk melestarikan budaya leluhur faktor lain yang mempengaruh adalah kurangnya kinerja pegawai dinas kebudayaan dalam menjaga kelestarian budaya khususnya di desa koto jayo.Kata Kunci : Sejarah Adat Istiadat Pernikahan, Desa Koto Jayo Kecamatan Tanah Tumbuh Kabupaten Bungo